Follow-Up of Child War-Related Post-Traumatic Stress Disorder and Other Psychiatric Disorders in Two Exposed Towns in Cundinamarca, Colombia (2012)
Objective: To determine the evolution of war-related posttraumatic stress disorder (PTSD), other psychiatric disorders, and associated factors, in school-aged children. METHODS Of 493 school-aged children evaluated initially in two war-exposed towns of Cundinamarca, Colombia, 148 children who were diagnosed with war-related PTSD, anxiety, or depression were invited to participate in a second follow-up assessment. Fifty-five children attended and were evaluated with a semi-structured psychiatric interview and the clinician-administered posttraumatic stress scale. RESULTS PTSD persisted in 50% of the children. Statistical associations were found between persistent PTSD and global child abuse (OR 017.8, 95% CI 02.73Á116.8), psychological child abuse (OR 016.0, 95% CI01.7Á154.6), psychosomatic disorder (OR 06.0, 95% CI01.2Á30.7), simple phobia (OR 06.0, 95% CI01.2Á30.7), learning disorder (P0.008), major depressive disorder (P0.021, Fisher exact test), and habitual alcohol consumption (P 0.050, Fisher exact test). Compared with the initial evaluation, this assessment found higher frequencies of anxiety disorder (73.3% vs 6.7%, McNemar test, PB.001) and child abuse (66.7% vs 20.0%, McNemar test, P0.008). Multivariate analysis found child abuse as predictor of persistent PSTD. CONCLUSIONS There was a high level of persistent war-related PSTD and child psychopathology. A civil population exposed to war events is at a high mental health risk. These children require urgent specialized mental health intervention in order to improve and to reduce long-term persistence of negative effects on their mental health. Child abuse prevention is essential for recovery from childhood PTSD